Clinical imipenem non-susceptible Klebsiella pneumoniae isolates from China: Epidemiology, molecular characterization and in vitro activity of imipenem/relebactam - Peiyao Jia; Pengcheng Li; Wei Yu; Xiaobing Chu; Hui Zhang; Jingjia Zhang; Wei Kang; Ge Zhang; Qian Zhang; Shiyu Chen; Yingchun Xu; Qiwen Yang (Journal of Global Antimicrobial Resistance)
Objective: To describe the epidemiological and molecular characterization and in vitro activity of imipenem/relebactam against imipenem non-susceptible (IPMNS) Klebsiella pneumoniae isolates in China. Methods: K. pneumoniae isolates were collected from 16 sites in 5 regions across China during 2019. Antimicrobial susceptibility testing was performed. For IPMNS K. pneumoniae isolates, whole genome sequencing was used to screen for drug-resistance and virulence genes. Results: Of 1011 clinical K. pneumoniae isolates, 277 (27.3%) were IPMNS and were significantly more common in intensive care unit patients (47.5%) and hospital-acquired infections (28.9%). Production of carbapenemase was the dominant resistance mechanism, with 228 (89.8%) IPMNS isolates harbouring blaKPC-2, 8 (3.1%) blaNDM, 2 (0.8%) blaOXA-232 and 1 (0.4%) blaOXA-181. The dominant clone was sequence type (ST) 11 (78.7%) followed by ST15 (10.2%). Relebactam restored imipenem’s susceptibility in 96.5% isolates harbouring a blaKPC-2 gene. Conclusions: Harbouring the blaKPC-2 gene was the dominant mechanism of IPMNS K. pneumoniae in China. Empirical imipenem/relebactam treatment could be considered when susceptibility or carbapenemase tests are not available.